Economic Mobility and the Rise of the Latin American Middle Class - Ferreira, Francisco H.G.; Messina, Julian; Rigolini, Jamele; López-Calva, Luis-Felipe; Lugo, Maria Ana; Vakis, Renos (Washington, DC: World Bank, 2012)
After decades of stagnation, the size of Latin America's middle class recently expanded to the point where, for the first time ever, the number of people in poverty is equal to the size of the middle class. This volume investigates the nature, determinants and possible consequences of this remarkable process of social transformation. We propose an original definition of the middle class, tailor-made for Latin America, centered on the concept of economic security and thus a low probability of falling into poverty. Given our definition of the middle class, there are four, not three, classes in Latin America. Sandwiched between the poor and the middle class there lies a large group of people who appear to make ends meet well enough, but do not enjoy the economic security that would be required for membership of the middle class. We call this group the 'vulnerable'.